The Divergent Effects of CDPPB and Cannabidiol on Fear Extinction and Anxiety in a Predator Scent Stress Model of PTSD in Rats - Shallcross, John; Hámor, Peter; Bechard, Allison R.; Romano, Madison; Knackstedt, Lori; Schwendt, Marek (Frontiers in Behavioral Neuroscience, 2019)
Post-traumatic stress disorder (PTSD) currently has no FDA-approved treatments that reduce symptoms in the majority of patients. The ability to extinguish fear memory associations is impaired in PTSD individuals. As such, the development of extinction-enhancing pharmacological agents to be used in combination with exposure therapies may benefit the treatment of PTSD. Both mGlu5 and CB1 receptors have been implicated in contextual fear extinction. Thus, here we tested the ability of the mGlu5 positive allosteric modulator 3-Cyano-N-(1,3-diphenyl-1H-pyrazol-5-yl)benzamide (CDPPB) and cannabidiol (CBD) to reduce both conditioned and unconditioned fear. We used a predator-threat animal model of PTSD which we and others have previously shown to capture the heterogeneity of anxiety responses observed in humans exposed to trauma. Here, 1 week following a 10-min exposure to predator scent stress, rats were classified into stress-Susceptible and stress-Resilient phenotypes using behavioral criteria for elevated plus maze and acoustic startle response performance. Two weeks after classification, rats underwent 3 days of contextual fear extinction and were treated with vehicle, CDPPB or CBD prior to each session. Finally, the light-dark box test was employed to assess phenotypic differences and the effects of CDPPB and CBD on unconditioned anxiety. CDPBB but not CBD, reduced freezing in Susceptible rats relative to vehicle. In the light-dark box test for unconditioned anxiety, CBD, but not CDPPB, reduced anxiety in Susceptible rats. Resilient rats displayed reduced anxiety in the light-dark box relative to Susceptible rats. Taken together, the present data indicate that enhancement of mGlu5 receptor signaling in populations vulnerable to stress may serve to offset a resistance to fear memory extinction without producing anxiogenic effects. Furthermore, in a susceptible population, CBD attenuates unconditioned but not conditioned fear. Taken together, these findings support the use of predator-threat stress exposure in combination with stress-susceptibility phenotype classification as a model for examining the unique drug response profiles and altered neuronal function that emerge as a consequence of the heterogeneity of psychophysiological response to stress.